NtMYB12 Positively Regulates Flavonol Biosynthesis and Enhances Tolerance to Low Pi Stress in Nicotiana tabacum - Song, Zhaopeng; Luo, Yong; Wang, Weifeng; Fan, Ningbo; Wang, Daibin; Yang, Chao; Jia, Hongfang (Frontiers in Plant Science, 2020)
Phosphorus (P) is an essential macronutrient for plant growth and development. The concentration of flavonol, a natural plant antioxidant, is closely related to phosphorus nutritional status. However, the regulatory networks of flavonol biosynthesis under low Pi stress are still unclear. In this study, we identified a PFG-type MYB gene, NtMYB12, whose expression was significantly up-regulated under low Pi conditions. Overexpression of NtMYB12 dramatically increased flavonol concentration and the expression of certain flavonol biosynthetic genes (NtCHS, NtCHI, and NtFLS) in transgenic tobacco. Moreover, overexpression of NtMYB12 also increased the total P concentration and enhanced tobacco tolerance of low Pi stress by increasing the expression of Pht1-family genes (NtPT1 and NtPT2). We further demonstrated that NtCHS-overexpressing plants and NtPT2-overexpressing plants also had increased flavonol and P accumulation and higher tolerance to low Pi stress, showing a similar phenotype to NtMYB12-overexpressing transgenic tobacco under low Pi stress. These results suggested that tobacco NtMYB12 acts as a phosphorus starvation response enhancement factor and regulates NtCHS and NtPT2 expression, which results in increased flavonol and P accumulation and enhances tolerance to low Pi stress.